Risikoorientierte Raumplanung in Österreich: Merkmale und Umsetzungsoptionen am Beispiel von Hochwasserrisiken. Issue 3 (3rd July 2018) - Seher, Walter; Löschner, Lukas
Abstract: Spatial planning plays a pivotal role in the nascent paradigm of flood risk management. By distributing land uses according to their suitability of location, spatial planning can limit the exposure and vulnerability of risk elements to flood hazards. Flood risk evaluation and subsequent land-use decisions are usually hazard-oriented, i.e. they are based on the spatial extension of flood events with a defined level of occurrence. Within these areas land development is prohibited or restricted, whereas outside of the defined hazard areas the development of floodplains is largely unchecked. In order to more effectively mitigate the future risks of flooding, however, there is a growing need to develop risk-oriented planning approaches that adjust land uses according to the probability and the intensity of flood hazards. In this paper we operationalise the concept of risk-oriented spatial planning and present a set of implementation options for flood-prone areas. These options are discussed with regard to their effectiveness and likelihood of practical implementation based on findings of an online survey among practitioners and scientific experts from the field of flood risk management. The survey response shows broad support for the proposed risk-oriented planning options, but also indicates a persistence of hazard-based approaches in Austrian flood risk management and a reluctance to introduce flood-adapted development in areas with low flood hazards. English title: Risk-Oriented Spatial Planning in Austria: Characteristics and Implementation Options in Flood Risk Management